Induction of Protective Immunity against Chlamydia trachomatis Genital Infection by a Vaccine Based on Major Outer Membrane Protein–Lipophilic Immune Response-Stimulating Complexes - Igietseme, Joseph U. (American Society for Microbiology, 2000)
The significance of delivery systems in modern vaccine design strategies is underscored by the fact that a promising vaccine formulation may fail in vivo due to an inappropriate delivery method. We evaluated the immunogenicity and efficacy of a candidate vaccine comprising the major outer membrane protein (MOMP) of Chlamydia trachomatis delivered with the lipophilic immune response-stimulating complexes (ISCOMs) as a vehicle with adjuvant properties, in a murine model of chlamydial genital infection. Immunocompetent BALB/c mice were immunized intranasally (IN) or intramuscularly (IM) with MOMP, MOMP-ISCOMs, and live or heat-inactivated C. trachomatis serovar D. The level of local genital mucosal Th1 response was measured by assaying for antigen-specific Th1 cell induction and recruitment into the genital mucosa at different times after immunization. Immunization with MOMP-ISCOMs by the IM route induced the greatest and fastest local genital mucosal Th1 response, first detectable 2 weeks after exposure. Among the other routes and regimens tested, only IN immunization with MOMP-ISCOMs induced detectable and statistically significant levels of local genital mucosal Th1 response during the 8-week test period (P < 0.001). In addition, when T cells from immunized mice were adoptively transferred into syngeneic naive animals and challenged intravaginally with Chlamydia, recipients of IM immunization of MOMP-ISCOMs cleared their infection within 1 week and were resistant to reinfection. Animals that received IN immunization of MOMP-ISCOMs were partially protected, shedding fewer chlamydiae than did control mice. Altogether, the results suggested that IM delivery of MOMP-ISCOMs may be a suitable vaccine regimen potentially capable of inducing protective mucosal immunity against C. trachomatis infection.